Bahan Ajar Berbasis STEM (Science, Technology, Engineering, and Mathematics) untuk Meningkatkan Penguasaan Konsep Siswa SMA (UPEJ Unnes Physics Education Journal, 2017)
The purpose of this study is to describe the characteristics of teaching materials based on STEM as well as to know the improvement of mastery of concept of high school students. The method used in this research is research and development. This research procedure is divided into four stages, i.e. preliminary study, planning, development and trial of teaching materials. Trial design using One Group Pretest-Posttest Design. The subjects of small and large group trials are XII MIPA 6 and XI MIPA 3 SMA Negeri 1 Wonosobo. Characteristics of STEM-based teaching materials containing dynamic fluid materials with practical problems and procedures and project preparation associated with STEM aspects. Result of feasibility test using questionnaire shows the instructional is suitable to be used. The result of readability test using cloze test shows the teaching material is easily understood. Teaching material can improve the mastery of student concepts characterized by the increase of pretest value to posttest.